A Cross-Sectional Geospatial Study on Families at Risk of Stunting in West Java - Cahyani, Restu Adya; Hastono, Sutanto Priyo (Health Notions, 2025)
Stunting affects the physical, cognitive, and overall health development of children under five, potentially hindering long-term economic growth. In West Java, stunting prevalence reached 21.7% in 2023, exceeding the WHO standard (<20%) and falling short of Indonesia’s target of 14%. This study aimed to develop a geospatial model to identify at-risk families and support targeted interventions, implemented by the Family Assistance Team (TPK). A cross-sectional research design using Quantum GIS with a scoring technique was employed. Data sources included the 2023 Indonesia Health Survey (SKI), the 2023 Ministry of Population and Family Development (BKKBN) data, and the BKKBN Family Information System. The study covered 27 districts/cities in West Java. Results showed high risk in 2 cities, with high stunting prevalence and low TPK assistance; moderate risk in 14 districts/cities with moderate stunting levels and varying TPK support; and low risk in 11 districts/cities with lower stunting prevalence and higher TPK coverage. The geospatial approach effectively mapped at-risk families and prioritized interventions, enhancing TPK effectiveness. This method supported evidence-based planning and cross-sector collaboration. The study concluded that geospatial analysis is a strategic tool for guiding targeted stunting interventions and optimizing resource allocation in West Java.